Natural gum reduced/stabilized gold nanoparticles for drug delivery formulations - Dhar, Sheetal; Reddy, E. Maheswara; Shiras, Anjali; Pokharkar, Varsha; Bhagavatula L. V. Prasad (Chemistry-A European Journal, 2008)
``Gellan Gum'', widely used in food and confectionary industry as a thickening and gelling agent, has been employed as a reducing and stabilizing agent for the synthesis of gold nanoparticles. These nanoparticles display greater stability to electrolyte addition and pH changes relative to the traditional citrate and borohydride reduced nanoparticles. Subsequently these have been used to load anthracycline ring antibiotic doxorubicin hydrochloride. The drug loaded on these nanoparticles showed enhanced cytotoxic effects on human glioma cell lines LN-18 and LN-229.
Keywords: Apoptosis; Cytotoxicity; drug delivery; Gold; Nanostructures; natural gums